The Effect Of Accounting Conservatism And Managerial Ownership Structure On Tax Avoidance - Desi Ratnasari; Erpi Rahman; Gunawan Wibisana (LPPM Universitas Sebelas April, 2019)
Tax avoidance is a legal way to reduce the tax burden owed. Tax avoidance can be measured using the Effective Tax Rate (ETR). This study was conducted to determine the effect of accounting conservatism and managerial ownership structure on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is descriptive quantitative. The data in this study uses secondary data in the form of consistent financial statements of manufacturing companies on the Indonesia Stock Exchange (IDX) for 2 periods from 2017-2018. sample using purposive sampling method. The number of samples selected were 8 observed companies. Data analysis used multiple linear regression. The results of this study prove that accounting conservatism has no effect on tax avoidance. This is because the use of inactive accounting will increase the company's tendency to take tax avoidance. And managerial ownership structure has no effect on tax avoidance. Because the portion of manager's share ownership is relatively low, it will not increase the company's tendency to do tax avoidance. Based on the tests carried out using the Simultaneous Test or the F test, the results of the statistical calculation of the F test above based on the Anova table show that Fcount is 0.870 > Ftable 0.267 and a significance value of 0.442 > 0.05